Assessment of semi-dynamic leaching characteristics of lead and zinc from stabilized contaminated soil using sustainable phosphate-based binder after carbonation. (15th January 2022) - Wei, Mingli; Li, Yuan; Yu, Bowei; Liu, Lei; Xue, Qiang; Du, Yanjun
Abstract: Stabilized contaminated soils face long-term complex environmental effects in the process of sustainable resource reuse. Therefore, semi-dynamic leaching tests in this study were conducted to investigate the leaching characteristics of novel sustainable phosphate binder stabilized soil contaminated with lead (Pb) and zinc (Zn) after carbonation in various simulated acid rain solutions to verify the sustainability of stabilization. Immobilization mechanisms of Pb and Zn, carbonation impact, leaching concentrations, pH, electrical conductivity, desorption parameters, leaching mechanisms, observed/effective diffusion coefficient ( D obs / D eff ), and leachability index were investigated. Complexation or adsorption of heavy metals can reduce the number of exchangeable ions, especially after carbonation. Carbonization showed a beneficial effect, indicating that the stabilized materials are a good carbon catcher. The leaching mechanism of Pb and Zn were all controlled by diffusion, which was caused by complex destruction and desorption. D obs values for Pb ranged from 10 −19 to 10 −16  m 2 /s, and those for Zn from 10 −17 to 10 −13  m 2 /s. Therefore, the mobilization of Zn was more intense than that of Pb. D eff values, calculated through the desorption parameter, were ∼3–4 orders of magnitude larger than D obs values. The leaching characteristics of Pb and Zn were influenced by leachant pH and carbonation, which were related to electrical conductivity and the cumulative leaching mass of magnesium. The effects had an influence on hydration products' chemical stability and buffering capacity. The stabilized materials can be used as recycled material in engineering, judging from the leachability index. This study can improve researchers' and engineers' understanding of the environmental leaching and toxicity of stabilized contaminated soil during reutilization, increasing reliability in reusing contaminated soil resources. Graphical abstract: Image 1 Highlight: Main HM complexes are Pb5 (PO4 )3 F and Zn3 (PO4 )2 ·4H2 O, even after carbonation HM-phosphate/carbonate have better acid resistance at pH = 5 and 7 compared with pH = 2 D obs of Pb and Zn are 10 −19 –10 −16 and 10 −17 –10 −13  m 2 /s, showing Zn is more active Carbonation increases acid buffer capacity and reduces D obs by ∼39–76% HM leaching mechanism is diffusion, caused by complex destruction and HM desorption